2017
DOI: 10.1016/j.omtn.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Knockout of the Vegfa Gene by Lentiviral Delivery of CRISPR/Cas9 in Mouse Retinal Pigment Epithelium Cells

Abstract: Virus-based gene therapy by CRISPR/Cas9-mediated genome editing and knockout may provide a new option for treatment of inherited and acquired ocular diseases of the retina. In support of this notion, we show that Streptococcus pyogenes (Sp) Cas9, delivered by lentiviral vectors (LVs), can be used in vivo to selectively ablate the vascular endothelial growth factor A (Vegfa) gene in mice. By generating LVs encoding SpCas9 targeted to Vegfa, and in parallel the fluorescent eGFP marker protein, we demonstrate rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 42 publications
1
50
0
Order By: Relevance
“…Finally, the sections were mounted on glass slides and coverslipped with Prolong Diamond mounting media (Thermofisher Scientific, Waltham, USA). The quality of staining of PV+ and VVA+ interneurons was evaluated using Zeiss LSM710/780 laser-scanning confocal microscopes controlled by ZEN 2009/2011 software (Carl Zeiss, Jena, Germany), respectively, as previously described 58 . 3-dimensional confocal images were taken by collecting stack images (135 μm × 135 μm) with a z-plane step size of 1.5 μm throughout the section depth giving a total of 14–16 stacks per image.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the sections were mounted on glass slides and coverslipped with Prolong Diamond mounting media (Thermofisher Scientific, Waltham, USA). The quality of staining of PV+ and VVA+ interneurons was evaluated using Zeiss LSM710/780 laser-scanning confocal microscopes controlled by ZEN 2009/2011 software (Carl Zeiss, Jena, Germany), respectively, as previously described 58 . 3-dimensional confocal images were taken by collecting stack images (135 μm × 135 μm) with a z-plane step size of 1.5 μm throughout the section depth giving a total of 14–16 stacks per image.…”
Section: Methodsmentioning
confidence: 99%
“…Advances in new imaging techniques allow for in vivo imaging that provides the opportunity for higher throughput and fully temporal measurements in various tissues. The latest in vivo gene editing techniques, such as CRISPR/Cas9, have made targeted genetic alterations easier, yet there are still challenges remaining with regards to efficiency and off‐target binding of genetic payloads . At the same time, advances in 3D bioprinting, biomaterial research, and patient‐specific primary cell culture allow for more advanced in vitro models, although there is still difficulty with cell collection in these systems for subsequent analysis .…”
Section: Markers and Models To Study Microvascular Network Architecturementioning
confidence: 99%
“… 30 , 31 So far, only a few studies have demonstrated in vivo gene editing following LV delivery of Cas9. 31 , 32 , 33 , 34 In this study, we chose LV as the delivery tool and suggested a better therapeutic efficacy over the renewal cycle of the epidermis. Then, the disrupted cytoskeletal integrity, abnormal differentiation, and irregular proliferation were ameliorated.…”
Section: Discussionmentioning
confidence: 99%